Doença de Still do adulto: como causa do síndrome febril indeterminado - Diogo, M (2010)
Fever of unknown origin remains a diagnostic challenge with up to 50% of unexplained cases. Adult-onset Still disease typically present high fever, arthralgia, rash, pharyngitis and serositis, lymphadenopathy and hepatosplenomegaly, inflammatory markers and hepatic enzymes elevation and negative immunological study. The authors present a 46-year old man with previous admissions for fever of unknown origin with a 3-week history of fever and systemic symptoms. The study disclosed anaemia, inflammatory markers and hepatic enzymes elevation, splenomegaly and negative serological and immunological studies. The patient posteriorly presented polyarthralgias and cutaneous rash. The introduction of corticotherapy resolved symptoms and laboratories alterations. Adult-onset Still disease is a heterogeneous and rare disease and the lack of serologic markers as a true gold standard makes diagnosis difficult.